2013
DOI: 10.1080/09658211.2012.756038
|View full text |Cite
|
Sign up to set email alerts
|

High-confidence memory errors in old age: The roles of monitoring and binding processes

Abstract: Based on a two-component model of episodic memory development across the lifespan, we examined the contribution of memory monitoring and binding processes to older adults' increased susceptibility to false memories with high subjective confidence. Younger and older adults worked on a modified version of the continuous recognition task (Schnider, von Daniken, & Gutbrod, 1996). Participants saw the same set of unrelated word pairs in three subsequent runs and had to identify pairs that were repeated within runs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
49
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 99 publications
8
49
1
Order By: Relevance
“…Our research contributes to the growing literature on memory distortions in aging (e.g., Balota, et al, 1999; Dennis, Kim, & Cabeza, 2008; Dodson & Schacter, 2002; Fandakova et al, 2013; Giovanello, Kensinger, Wong, & Schacter, 2010; Jacoby, Bishara, Hessels, & Toth, 2005; Rosa & Gutchess, 2013; Koutstaal & Schacter, 1997; Schacter, Israel, & Racine, 1999; Tun, Wingfield, Rosen, & Blanchard, 1998), particularly on tasks involving false memories for information presented after study. For example, in the postevent misinformation paradigm (for review see Loftus, 2005), older adults are generally more susceptible to falsely recalling erroneous information presented during misinformation on a subsequent memory test (e.g., Cohen & Faulkner, 1989; Karpel, Hoyer, & Toglia, 2001; Loftus, Levidow, & Duensing, 1992; but see Coxon & Valentine, 1997).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Our research contributes to the growing literature on memory distortions in aging (e.g., Balota, et al, 1999; Dennis, Kim, & Cabeza, 2008; Dodson & Schacter, 2002; Fandakova et al, 2013; Giovanello, Kensinger, Wong, & Schacter, 2010; Jacoby, Bishara, Hessels, & Toth, 2005; Rosa & Gutchess, 2013; Koutstaal & Schacter, 1997; Schacter, Israel, & Racine, 1999; Tun, Wingfield, Rosen, & Blanchard, 1998), particularly on tasks involving false memories for information presented after study. For example, in the postevent misinformation paradigm (for review see Loftus, 2005), older adults are generally more susceptible to falsely recalling erroneous information presented during misinformation on a subsequent memory test (e.g., Cohen & Faulkner, 1989; Karpel, Hoyer, & Toglia, 2001; Loftus, Levidow, & Duensing, 1992; but see Coxon & Valentine, 1997).…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have shown that older adults recall less accurate memories and are more susceptible to various errors and distortions in memory (for reviews, see Fandakova, Shing, & Lindenberger, 2013; Jacoby & Rhodes, 2006; Koutstaal & Schacter, 2001; Schacter, Koutstaal, & Norman, 1997). Aging also impairs subjective recollection processes and contextual recall (for review see Spencer & Raz, 1995; Yonelinas, 2002), which contribute to the quality of memory reactivation.…”
mentioning
confidence: 99%
“…Younger and older adults with poor performance on behavioral tests reliant on MTL functioning are more likely to falsely identify lure items on the basis of semantic relatedness or familiarity with studied items (Fandakova et al, 2013b; Plancher et al, 2009; Rubin et al, 1999; see also Zhu et al, 2010), though the evidence for this relationship is mixed (McCabe et al, 2009). Likewise, performance on executive functioning tests sensitive to frontal functioning (particularly dorsolateral and superior medial PFC; see Stuss et al, 1998, 2000, 2001; Troyer et al, 1998) is associated with deficits in monitoring the source of incoming information for both younger and older adults (Chan & McDermott, 2007; Craik et al, 1990; Fandakova et al, 2013a; Glisky et al, 2001; Henkel et al, 1998; Pansky et al, 2009; Plancher et al, 2009; Roediger & Geraci, 2007; Rubin et al, 1999; Sauzéon et al, 2016). Highlighting the considerable heterogeneity in cognitive aging, older adults with preserved executive functioning are no more susceptible to false alarms than college students (Butler et al, 2004; Meade et al, 2012; though see Lindner & Davidson, 2014).…”
Section: Medial Temporal Lobe and Prefrontal Cortex Changes With Amentioning
confidence: 99%
“…First, older adults may have difficulty monitoring retrieval attempts (e.g., Fandakova, Shing, & Lindenberger, 2013a, 2013b). In this case, the hippocampus may fail to access the correct information, possibly due to a failure in binding the details together (Naveh-Benjamin, 2000).…”
mentioning
confidence: 99%